Recyclable label

The recyclable label addresses the backtrap phenomenon by incorporating particulate matter with specific size ranges in the coating layer, ensuring proper ink printing and label quality.

JP2025059633APending Publication Date: 2025-04-10DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023169849
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing recyclable labels with fluorescent materials in the alkali-soluble coating layer suffer from a backtrap phenomenon when further ink is applied, leading to improper ink printing and no description is provided on the relationship between lubricating particles and this phenomenon.

Method used

A recyclable label comprising a substrate, a coating layer with a resin having an acid value of 40 mgKOH/g or more and 150 mgKOH/g or less, and a fluorescent material, along with particulate matter with an average particle size greater than 1 μm and less than 100 μm, which suppresses the backtrapping phenomenon and ensures proper ink printing.

Benefits of technology

The solution effectively prevents the backtrapping phenomenon, allowing for a suitable formation of the ink printing layer on the coating layer, while also maintaining the beauty and transparency of the label.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059633000001_ABST
    Figure 2025059633000001_ABST
Patent Text Reader

Abstract

To provide a recyclable label in which an ink printing layer is appropriately formed on a coat layer containing a resin having alkali solubility and a fluorescent material.SOLUTION: A recyclable label 1 comprises a substrate 11, a coat layer 12, and an ink printing layer 13. The coat layer 12 is provided on the substrate 11 and contains a resin, of which the acid value is from 40 mgKOH / g or more to 150 mgKOH / g or less, and a fluorescent material. The ink printing layer 13 is positioned on the coat layer 12 at an opposite side of the substrate 11 in a view from the coat layer 12. The coat layer 12 further contains a granular material. An average particle diameter of the granulate material exceeds 1 μm and is equal to or less than 100 μm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to recyclable labels. [Background technology]

[0002] International Publication No. 2021 / 246230 (Patent Document 1) discloses a label that contains a material that emits light when irradiated with energy rays and that allows the ink layer to be removed by alkali desorption. The label includes a substrate, an alkali-soluble coating layer on the substrate, and an ink layer on the coating layer. The coating layer further contains a material that emits light when irradiated with energy rays. This makes it possible to identify and separate the label that has an alkali-soluble coating layer by irradiating the label with energy rays and causing it to emit light. For example, a fluorescent pigment or a phosphorescent pigment can be used as the material.

[0003] JP 2019-127536 A (Patent Document 2) discloses that adhesion is improved by providing an easy-adhesion resin layer on the surface of a polyester film. The easy-adhesion resin layer may contain lubricant particles to impart slipperiness to the surface. Examples of the particles include inorganic particles such as silica. It is disclosed that an average particle size of the particles of 10 nm or more is preferable because it is difficult to aggregate and slipperiness can be ensured. It is disclosed that an average particle size of the particles of 1000 nm or less is preferable because transparency is maintained and the particles do not fall off. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2021 / 246230 [Patent Document 2] JP 2019-127536 A Summary of the Invention [Problem to be solved by the invention]

[0005] As described in Patent Document 1, when a fluorescent material is added to an alkali-soluble coating layer on a substrate, a back-trap phenomenon may occur when ink is further applied (printed) on the coating layer. That is, when a coating layer composition containing a fluorescent material is applied to a substrate and ink is applied (printed) on the coating layer after a predetermined drying time has elapsed, a part of the surface layer of the coating layer that contacted the ink is detached and re-dissolved in the ink on the printing plate. As a result, the ink is not properly printed on the part where the part of the coating layer is detached. In addition, Patent Document 2 does not disclose any relation between the lubricating particles that may be contained in the easy-adhesion resin layer and the back-trap phenomenon described above.

[0006] The present disclosure has been made in consideration of the above-mentioned problems, and aims to provide a recyclable label in which an ink printing layer is appropriately formed on a coating layer containing an alkali-soluble resin and a fluorescent material. [Means for solving the problem]

[0007] A recyclable label according to the present disclosure includes a substrate, a coating layer, and an ink-printed layer. The coating layer is provided on the substrate, and includes a resin having an acid value of 40 mgKOH / g or more and 150 mgKOH / g or less, and a fluorescent material. The ink-printed layer is located on the coating layer on the opposite side of the substrate from the coating layer. The coating layer further includes particulate matter. The particulate matter has an average particle size of more than 1 μm and not more than 100 μm.

[0008] In the above-mentioned recyclable label, the coating layer further contains particulate matter having an average particle diameter of more than 1 μm. As a result, when a coating layer composition for forming the coating layer is applied onto a substrate, the particulate matter having an average particle diameter of more than 1 μm contained in the coating layer composition forms unevenness on the surface of the coating layer. As a result, even if the coating layer contains a fluorescent material, when ink is applied (printed) onto the coating layer, the contact state between the plate for applying the ink and the coating layer is changed compared to when the coating layer does not contain particulate matter, so that the occurrence of the back trap phenomenon is suppressed. In addition, a recyclable label in which an ink printing layer is appropriately formed on the coating layer can be provided.

[0009] In addition, by making the average particle size of the particulate matter 100 μm or less, it is possible to prevent the surface of the coating layer from becoming too uneven, which in turn prevents the ink printing layer on the coating layer from becoming smudged, and thus prevents the cosmetic appearance of the label from being deteriorated. Effect of the Invention

[0010] According to the present disclosure, it is possible to provide a recyclable label in which an ink-printed layer is appropriately formed on a coating layer containing an alkali-soluble resin and a fluorescent material. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a schematic cross-sectional view of a label according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic diagram showing a state in which an energy ray is irradiated to a label according to an embodiment of the present disclosure in a predetermined dark place. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the configuration of a label according to an embodiment of the present disclosure will be described with reference to the drawings. In the following description of the embodiment, the same or corresponding parts in the drawings are denoted by the same reference characters, and the description thereof will not be repeated.

[0013] A label according to an embodiment of the present disclosure includes a substrate, a coating layer, and an ink-printed layer. The label according to an embodiment of the present disclosure is recyclable. Here, a recyclable label refers to a label in which all or a part of the raw materials, such as the substrate and the pigment of the ink-printed layer, are recyclable. The coating layer is provided on the substrate, and contains a resin having an acid value of 40 mgKOH / g or more and 150 mgKOH / g or less, and a fluorescent material. The ink-printed layer is located on the coating layer on the opposite side of the substrate from the coating layer. The coating layer further contains particulate matter. The particulate matter has an average particle size of more than 1 μm and not more than 100 μm.

[0014] In this embodiment, by using a fluorescent material, it is possible to distinguish between labels using a fluorescent material that can be removed by alkali and labels not using a fluorescent material that cannot be removed by alkali. In addition, the back trap phenomenon caused by the addition of a fluorescent material can be suppressed by adding a particulate material with an average particle diameter of more than 1 μm. Furthermore, it is easy to confirm the remaining fluorescent material on the substrate after the coating layer is removed, and a substrate from which the coating layer has been completely removed can be obtained by not detecting the fluorescent material. The recyclable label according to this embodiment fully possesses various physical properties possessed by conventional labels. When this recyclable label is immersed in a 1.5% by mass sodium hydroxide aqueous solution heated to 80 to 90°C and stirred for 15 minutes, the coating layer is easily removed from the substrate, and after the coating layer is removed, it is possible to obtain a clean substrate with almost no coating layer remaining by washing with water and drying.

[0015] (label) FIG. 1 is a schematic cross-sectional view of a label according to an embodiment of the present disclosure. As shown in FIG. 1, the label 1 according to the embodiment of the present disclosure includes a substrate 11, an alkali-soluble coating layer 12 on the substrate 11, and an ink printing layer 13 on the coating layer 12. The label 1 according to the embodiment may be a label having heat shrinkability (shrink label) or a label having no heat shrinkability. The label 1 according to the embodiment of the present disclosure may be a stretch label having self-stretchability or a label having no self-stretchability. The label 1 according to the embodiment of the present disclosure may be a wrap-around label (roll label), a wrap-around shrink label (ROSO label), an in-mold label, a heat-sensitive label, a tack label, or the like.

[0016] <Base material> The substrate 11 has a film-like outer shape. The substrate 11 may be a resin substrate or a paper substrate, but is a recyclable substrate. Therefore, the label 1 according to this embodiment can be recycled. When the substrate 11 is a resin substrate, examples of the resin contained in the substrate 11 include polyester-based resins (polyethylene terephthalate, polyethylene naphthalate, polylactic acid, etc.), polystyrene-based resins (polystyrene, styrene-butadiene copolymer, etc.), polyolefin-based resins (polyethylene-based resins, polypropylene-based resins, etc.), polyvinyl chloride-based resins, polyamide-based resins, aramid-based resins, polyimide-based resins, polyphenylene sulfide-based resins, and acrylic-based resins. The substrate 11 may contain one type of these resins, or may contain two or more types.

[0017] The resin contained in the base material 11 is preferably a polyester resin, and particularly preferably a polyethylene terephthalate resin (PET). PET is a polyester resin containing terephthalic acid as the main component of the dicarboxylic acid component and ethylene glycol as the main component of the diol component. PET may also contain, as other components, dicarboxylic acids such as isophthalic acid, phthalic acid, adipic acid, sebacic acid, or naphthalenedicarboxylic acid, and may also contain diol components such as diethylene glycol, neopentyl glycol, polyalkylene glycol, or 1,4-cyclohexanedimethanol. The resin contained in the base material 11 is also preferably a polyolefin resin, and more preferably a polyethylene resin or a polypropylene resin.

[0018] The substrate 11 may be, for example, a film having heat shrinkability (shrink film). When the substrate 11 is a shrink film, it is possible to improve the processability (ability to conform to the container) and decorativeness of the label 1, and to further increase the display area of ​​the label 1. The substrate 11 may also be, for example, a stretch film having self-stretchability.

[0019] The substrate 11 may be a single-layer film made of one layer, or may be a multi-layer film made of two or more layers. The thickness of the substrate 11 may be, for example, 5 μm to 100 μm, but is not particularly limited.

[0020] <Coat layer> The coating layer 12 is a layer containing an alkali-soluble resin, and the coating layer 12 is alkali-soluble. The coating layer 12 is provided on the substrate 11. Specifically, the coating layer 12 is located between the substrate 11 and the ink printing layer 13. The coating layer 12 may be provided only on a part of one surface of the substrate 11, but from the viewpoint of increasing the amount of light emitted by the fluorescent material described below, it is preferable that the coating layer 12 is provided on the entire one surface of the substrate 11.

[0021] The coating layer 12 (resin) being alkali-soluble means that when a sample having a coating layer 12 (resin coating) measuring 4 cm x 4 cm formed on a substrate 11 of any size is immersed in a 1.5 mass% sodium hydroxide aqueous solution (i.e., 1.5% of the total mass of the sodium hydroxide aqueous solution is sodium hydroxide) at 85°C and stirred at 1500 rpm, 70% or more of the total area of ​​the coating layer 12 (resin coating) will be detached from the sample after an immersion time of 15 minutes.

[0022] In this embodiment, the resin contained in the coating layer 12 has an acid value of 40 mgKOH / g or more and 150 mgKOH / g or less. This makes the resin alkali-soluble. As the resin contained in the coating layer 12, for example, a resin having the following (1) to (4) can be used. (1) containing a first resin which is an acrylic acid copolymer resin having a first glass transition temperature T1; (2) containing a second resin which is an acrylic acid copolymer resin having a second glass transition temperature T2 lower than the above T1; (3) the apparent acid value of the coating layer 12 is 40 mgKOH / g or more and 150 mgKOH / g or less; (4) The first resin and the second resin contained in the coating layer 12 account for 50 to 95% by mass in total of the coating layer 12 .

[0023] Resins having the above (1) to (4) have good alkali solubility. Therefore, when the label 1 has the alkali-soluble coating layer 12 between the substrate 11 and the ink-printed layer 13, the ink-printed layer 13 is also detached from the substrate 11 as the coating layer 12 is detached from the label 1 by alkali.

[0024] As shown in (1) and (2) above, the first resin and the second resin are each an acrylic acid copolymer resin. The acrylic acid copolymer resin is a resin that contains acrylic acid and / or methacrylic acid as a main repeating unit and also contains a copolymerizable monomer copolymerizable with the acrylic acid and / or methacrylic acid. The acrylic acid copolymer resin preferably has a total ratio of acrylic acid and / or methacrylic acid and the copolymerizable monomer in the resin of 60 mol % or more.

[0025] Examples of the copolymerizable monomer include (meth)acrylic acid alkyl esters (preferably lower alkyl esters of (meth)acrylic acid) such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and t-butyl (meth)acrylate; hydroxyl group-containing (meth)acrylates such as hydroxyethyl (meth)acrylate; glycidyl group-containing (meth)acrylates such as glycidyl (meth)acrylate; N,N'-dimethyl (meth)acrylic acid amines; Examples of the copolymerizable monomer include (meth)acrylamides such as N,N'-diethyl(meth)acrylamide, amino group-containing (meth)acrylates such as dimethylaminoethyl(meth)acrylate, styrenes such as styrene, vinyl toluene, α-methylstyrene, vinyl esters such as vinyl acetate and vinyl propionate, vinyl halides such as vinyl chloride, vinyl ethers such as methyl vinyl ether, carboxyl group-containing vinyls such as itaconic acid and maleic anhydride [excluding (meth)acrylic acid], cyano group-containing vinyls such as acrylonitrile and methacrylonitrile, olefins and dienes such as ethylene and propylene, etc. The copolymerizable monomers can be used alone or in combination of two or more.

[0026] Regarding the above (1) and (2), the glass transition temperatures of the first resin and the second resin can be controlled, for example, by adjusting the mass average molecular weight (Mm) of the acrylic acid copolymer resin. For example, the first resin and the second resin can be made to have a relationship of T1>T2 by making the Mm of the first resin larger than that of the second resin. Preferably, the Mm of the first resin is 30,000 or more and 90,000 or less, and the Mm of the second resin is 10,000 or more and less than 30,000. When the Mm of the first resin is 30,000 or more, it is preferable because the adhesion is good. When the Mm of the first resin is 90,000 or less, it is preferable because the composition for forming the coat layer does not become stringy in the non-printed parts at both ends of the plate in the case of gravure printing, for example. In addition, when the Mm of the first resin is 90,000 or less, it is preferable because the viscosity of the composition for forming the coat layer does not increase excessively. When the Mm of the second resin is 10,000 or more, it is preferable because the adhesion is good. If the second resin has an Mm of 30,000 or less, when the label 1 is used as a shrink label, for example, whitening due to shrinkage can be suppressed when the shrink label is shrunk, which is preferable.

[0027] Regarding the above (1) and (2), T1, which is the glass transition temperature of the first resin, is preferably 90°C or higher, more preferably 95°C or higher, and particularly preferably 100°C or higher. The upper limit of T1 can be, for example, about 120°C, from the physical properties of the acrylic acid copolymer resin. T2, which is the glass transition temperature of the second resin, is preferably less than 80°C, more preferably 75°C or lower, and particularly preferably 65°C or lower. The lower limit of T2 can be, for example, about 30°C, from the viewpoint of ease of handling. For example, it is preferable that there is a difference between T1 and T2 of 20°C or higher, more preferably a difference of 30°C or higher, and particularly preferably a difference of 40°C or higher. In this case, the deterioration of printability can be more effectively suppressed, and therefore the cosmetic properties of the ink-printed layer 13 can be particularly improved.

[0028] With regard to the above (3), the apparent acid value of the coating layer 12 means the acid value of a mixed resin consisting of two or more kinds of resins contained in the coating layer 12. The apparent acid value of the coating layer 12 can be adjusted by controlling the acid values ​​of the first resin and the second resin. The acid values ​​of the first resin and the second resin can be adjusted, for example, by the blending ratio of (meth)acrylic acid and the copolymerizable monomer.

[0029] Regarding the above (3), the apparent acid value of the coating layer 12 is more preferably from 50 mgKOH / g to 130 mgKOH / g, and particularly preferably from 55 mgKOH / g to 125 mgKOH / g, which can particularly improve the alkali solubility and printability of the coating layer 12.

[0030] The acid value of the first resin and the acid value of the second resin are preferably 40 mgKOH / g or more and 150 mgKOH / g or less. In this case, the apparent acid value of the coating layer 12 can be easily set to 40 mgKOH / g or more and 150 mgKOH / g or less as in (3) above. From the viewpoint of the alkali resistance of the label, it is preferable that each acid value is less than 150 mgKOH / g. From the viewpoint of alkali release function and adhesion, it is preferable that each acid value is 40 mgKOH / g or more. In addition, it is preferable that the acid value of the first resin is lower than the acid value of the second resin. The acid value of the first resin is preferably less than 60 mgKOH / g. In addition, it is preferable that the acid value of the second resin is 80 mgKOH / g or more.

[0031] With regard to the above (4), the first resin and the second resin in the coating layer 12 preferably account for 70% by mass or more and 95% by mass or less of the entire coating layer 12, and more preferably for 80% by mass or more and 95% by mass or less. In these cases, it is possible to particularly improve the alkali solubility and printability of the coating layer 12. Also, it is preferable that the content ratio of the first resin and the content ratio of the second resin are not significantly different. From the viewpoint of improving the synergistic effect of containing two types of resin, the first resin and the second resin, it is preferable that the ratio of the content of the first resin to the content of the second resin (the content of the resin with a relatively large content / the content of the resin with a relatively small content) is 3 or less.

[0032] The fact that the coating layer 12 contains an alkali-soluble resin can be confirmed, for example, by using various analytical techniques. For example, it can be confirmed that the acrylic acid copolymer resin is present in the coating layer 12 at a specific content by nuclear magnetic resonance (NMR), gas chromatography mass spectrometry (GCMS), pyrolysis gas chromatography (pyrolysis GCMS), etc. Also, the acid value of the coating layer 12 can be confirmed, for example, by titrating the coating layer 12. The titration of the coating layer 12 can be calculated based on the result of dissolving the coating layer 12 in a titration solvent such as a mixed solvent of xylene and dimethylformamide, and performing potentiometric titration using a potassium hydroxide solution of a predetermined concentration (for example, a 0.1 mol / L potassium hydroxide-ethanol solution). Also, it can be confirmed that the coating layer 12 contains the first resin and the second resin having the above Tg, for example, by subjecting a composition used to form the coating layer described below to a differential scanning calorimetry (DSC) method. The DSC method can be performed using a "DSC6200" manufactured by Seiko Instruments Inc. at a temperature rise rate of 10°C / min. The Mm of the first resin and the Mm of the second resin can be confirmed by, for example, gel permeation chromatography (GPC).

[0033] The first and second resins are preferably methacrylic acid-methyl methacrylic acid copolymers (hereinafter, also referred to as "MM copolymers"). In this case, it is possible to significantly improve both the alkali solubility and printability of the coating layer 12. The MM copolymer may be a synthesized product or a commercially available product.

[0034] The coating layer 12 may contain other components in addition to the first resin and the second resin. A preferred example of the other components is a cellulose derivative. When the coating layer 12 contains a cellulose derivative, it is possible to improve the blocking resistance and adhesion of the coating layer 12.

[0035] Examples of the cellulose derivative contained in the coating layer 12 include nitrocellulose, acetylcellulose, carboxymethylcellulose or a salt thereof, methylcellulose, hydroxypropylmethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, cellulose acetate butyrate, and cellulose acetate propionate. It is preferable to use nitrocellulose as the cellulose derivative contained in the coating layer 12. In the coating layer 12, the cellulose derivative may be used alone or in combination of two or more kinds.

[0036] The content of the cellulose derivative in the coating layer 12 is preferably 1% by mass or more and 20% by mass or less, more preferably 5% by mass or more and 15% by mass or less, and particularly preferably 8% by mass or more and 12% by mass or less, based on the total mass of the coating layer 12. In these cases, the blocking resistance and printability of the coating layer 12 can be improved. The cellulose derivative preferably has a degree of polymerization of 35 to 380, more preferably 45 to 290, and particularly preferably 55 to 110. In these cases, the blocking resistance and printability of the coating layer 12 can be improved.

[0037] Furthermore, the coating layer 12 may contain, for example, a vinyl chloride-vinyl acetate copolymer (hereinafter, also referred to as a "VV copolymer") as a preferred other component. When the coating layer 12 contains a VV copolymer, it is possible to further improve the adhesion between the substrate 11 and the coating layer 12.

[0038] The content of the VV copolymer in the coating layer 12 is preferably 5 to 20 mass % of the total mass of the coating layer 12, more preferably 8 to 18 mass %, and particularly preferably 9 to 12 mass %. In these cases, the adhesion and printability of the coating layer 12 can be improved. The VV copolymer in the coating layer 12 preferably has an Mm of 10,000 to 40,000, and more preferably has an Mm of 15,000 to 35,000. In these cases, the adhesion of the coating layer 12 is significantly improved.

[0039] In the label 1 according to the embodiment of the present disclosure, the coating layer 12 contains a fluorescent material. A fluorescent material is a material that emits light when irradiated with energy rays, but does not include materials that have phosphorescence. The fluorescent material is, for example, a fluorescent dye such as a fluorescent brightener, or a fluorescent pigment. In this embodiment, the fluorescent material is preferably a fluorescent brightener.

[0040] Fluorescent brightening agents are a type of fluorescent dye. They absorb energy rays (specifically ultraviolet rays) and emit a pale blue light. Fluorescent dyes are used to dye resins. For this reason, fluorescent brightening agents can make a coating layer glow with a relatively small content relative to an alkali-soluble resin, compared to fluorescent pigments.

[0041] When a fluorescent whitening agent is used as the fluorescent material, it is preferable that the fluorescent whitening agent is one that is highly safe for living organisms and has high light resistance. In this embodiment, the fluorescent whitening agent may be a benzoxazole-based compound or the like. Alternatively, the fluorescent whitening agent may be, for example, a naphthalene benzoxazolyl derivative, a thiophene benzoxazolyl derivative, a stilbene benzoxazolyl derivative, a coumarin derivative, a styrene biphenyl derivative, a pyrazolone derivative, a stilbene derivative, a styryl derivative of benzene and biphenyl, a bis(benzazol-2-yl) derivative, a carbostyryl, a naphthalimide, a derivative of dibenzothiophene-5,5'-dioxide, a pyrene derivative, and a pyridotriazole. The fluorescent whitening agent may be used alone in one or more kinds, or in combination in two or more kinds.

[0042] The fluorescent whitening agent may be a commercially available product. Examples of the commercially available fluorescent whitening agent include TELALUX (registered trademark) OB (2,5-bis(5-tert-butyl-2-benzoxazolyl)thiophene) and KCB (1,4-bis(2-benzoxazolyl)naphthalene) from Clariant Japan.

[0043] When a fluorescent pigment is used as the fluorescent material, examples of the fluorescent pigment include organic pigments and inorganic pigments. Examples of the organic pigments include fluorescein-based, coumarin-based, rhodamine-based, oxazole-based, pyrazoline-based, thiadiazole-based, spiropyran-based, pyrenesulfonic acid-based, benzimidazole-based, and diaminostilbene-based compounds. Examples of the inorganic pigments include zinc sulfide activated with copper, silver, manganese, and the like, zinc silicate activated with manganese, and the like, calcium sulfide activated with cadmium, bismuth, and the like, strontium sulfide activated with samarium, cerium, and the like, and calcium tungstate activated with lead, and the like.

[0044] As the fluorescent pigment, for example, one of the above types may be used alone, or two or more of the above types may be used in combination. The average particle size of the fluorescent pigment is preferably 1 μm or more and 20 μm or less, and more preferably 5 μm or more and 15 μm or less. When the average particle size of the fluorescent pigment is 1 μm or more, the aggregation of the fluorescent pigment is suppressed, the coating film becomes more uniform, and the influence on the cosmetic properties of the label can be reduced, which is preferable. When the average particle size of the fluorescent pigment is 20 μm or less, the fluorescent pigment is more easily dispersed in the coating layer, and the occurrence of aggregation and sedimentation of the fluorescent pigment can be suppressed, which is preferable. In this specification, the "average particle size" of the fluorescent material is measured by measuring the particle size distribution based on volume in advance, and is measured as the particle size at which the cumulative frequency from the side with the small particle size reaches 50%. Specifically, the average particle size of the fluorescent material is measured by a laser diffraction method.

[0045] For example, a fluorescent material having a maximum absorption wavelength of 300 nm or more and 400 nm or more can be used. The maximum absorption wavelength refers to the wavelength at which the absorbance is greatest in the absorption spectrum, which shows the relationship between the wavelength of light absorbed by the fluorescent material and the absorbance at that wavelength. For example, a fluorescent material having a maximum fluorescence wavelength of 400 nm or more and 450 nm or less can be used. The maximum fluorescence wavelength refers to the wavelength at which the intensity is greatest in the emission spectrum, which shows the relationship between the wavelength of light emitted by the fluorescent material due to absorption and the intensity of that light at that wavelength.

[0046] The content of the fluorescent material in the coating layer 12 is, for example, 0.3% by mass or more and 8.0% by mass or less. If the content of the fluorescent material in the coating layer 12 is 0.3% by mass or more, the label 1 according to the present disclosure can be sufficiently distinguished from a label to which no fluorescent material is added by the emission of the fluorescent material when the label 1 is irradiated with ultraviolet light. If the content is 8.0% by mass or less, the deterioration of the printability of the composition for forming the coating layer can be suppressed. From the viewpoint of distinguishability, the content of the fluorescent material is more preferably 1.0% by mass or more. From the viewpoint of printability, the content of the fluorescent material is more preferably 5.0% by mass or less.

[0047] The content of the fluorescent material in the composition for forming the coat layer is, for example, 0.1 parts by mass or more and 3.0 parts by mass or less in 100 parts by mass of the composition for forming the coat layer. If the content is 0.1 parts by mass or more, the label 1 according to the present disclosure can be sufficiently distinguished from a label to which no fluorescent material is added by the emission of the fluorescent material when the label 1 is irradiated with ultraviolet light. If the content is 3.0 parts by mass or less, the deterioration of the printability of the composition for forming the coat layer can be suppressed. From the viewpoint of distinguishability, the content of the fluorescent material is more preferably 0.3 parts by mass or more. From the viewpoint of printability, the content of the fluorescent material is more preferably 1.0 parts by mass or less. If the content of the fluorescent material is 0.1 parts by mass or more, the fluorescence intensity becomes larger and the detection of the emission becomes easier. If the content of the fluorescent material is 3.0 parts by mass or less, the occurrence of a bluish color due to sunlight or the like is suppressed, and the influence on the cosmetic properties of the label can be reduced. In addition, the lower the content of the fluorescent material, the less likely the back trap phenomenon occurs.

[0048] In this embodiment, the coating layer 12 further contains solid particulate matter. As a result, unevenness is formed on the surface of the coating layer 12 due to the addition of the particulate matter. As a result, when the ink resin composition is further applied onto the coating layer 12, the contact state between the plate for applying the ink resin composition and the coating layer 12 changes compared to when the coating layer does not contain the particulate matter. Specifically, the formation of the unevenness makes it difficult for a closed space of negative pressure to be formed between the plate and the coating layer. Therefore, the coating layer 12 is prevented from being peeled off by the plate, and the occurrence of the back trap phenomenon is suppressed.

[0049] The particulate matter preferably has high translucency and is preferably colorless or white, which can prevent a decrease in visibility of the ink-printed layer 13 through the coating layer 12 when the label 1 is viewed from the substrate 11 side.

[0050] The shape of the particulate material is not particularly limited. The particulate material may be spherical or approximately spherical, or may be non-spherical. The particulate material may be hollow particles. The particulate material may be surface-treated. When the particulate material is surface-treated with a substance different from the particulate material, the content of the particulate material described below is treated as the total content of the other substance and the particulate material.

[0051] The material constituting the particulate matter is not particularly limited. The particulate matter may be either organic particles containing an organic compound or inorganic particles containing an inorganic compound, but is preferably inorganic particles from the viewpoint of dispersibility in the composition for forming the coating layer.

[0052] Examples of the inorganic particles include particles made of inorganic compounds. Examples of the inorganic compounds include inorganic oxides such as titanium oxide, aluminum oxide (alumina), silicon oxide (silica), magnesium oxide, zinc oxide, and barium titanate; inorganic nitrides such as silicon nitride, boron nitride, and aluminum nitride; inorganic fluorides such as magnesium fluoride and calcium fluoride, and inorganic salts such as calcium carbonate and barium sulfate; and glass. Among these, the particulate material is preferably silica. Silica is easy to handle and can effectively suppress the decrease in transparency of the coating layer 12. In addition, silica is excellent in safety when recycling the substrate 11. Furthermore, silica has a Mohs hardness of about 7, which is an appropriate hardness. This makes it suitable for forming a coating film when forming a coating layer. Furthermore, when the particulate material is silica, the silica can exist in the coating layer 12 in an aggregated state as secondary particles.

[0053] Examples of organic particles include resin particles made of (meth)acrylic resin (so-called acrylic beads), resin particles made of styrene resin, and the like.

[0054] In this embodiment, the average particle diameter of the particulate matter is more than 1 μm and 100 μm or less. If the average particle diameter of the particulate matter is 1 μm or less, the back trap phenomenon cannot be sufficiently suppressed. If the average particle diameter of the particulate matter is more than 100 μm, when ink is printed on the part where the particulate matter is located, the ink may be slightly missing from the part, causing the ink printing layer 13 to be smudged. This reduces the aesthetic value of the label 1. In addition, the smaller the average particle diameter of the particulate matter, the more the haze value of the coating layer 12 is suppressed from increasing, so that the effect on the color of the ink printing layer 13 is suppressed, and the more uniform the ink printing layer 13 can be obtained. In this specification, the average particle diameter of the particulate matter is the number average diameter, which means the arithmetic mean diameter based on the number. The average particle diameter of the particulate matter can be measured as follows. First, the coating layer is imaged from the substrate 11 side of the label 1 using a microscope (for example, a digital microscope). The captured image is analyzed to measure the diameter of each of a number of randomly selected particulate matter particles (if the particulate matter is not spherical, the diameter of the circle equivalent to the projected area). The diameters of each of the measured particulate matter particles are arithmetically averaged on a number basis. This gives the average particle size of the particulate matter.

[0055] The content of the particulate matter in the coating layer 12 is preferably, for example, 0.1% by mass or more and 5% by mass or less. If the content of the particulate matter is 0.1% by mass or more, the back trapping phenomenon can be more effectively suppressed. If the content of the particulate matter is 5% by mass or less, the decrease in transparency of the coating layer 12 can be suppressed, and the coating layer 12 can be suppressed from becoming matte. From the viewpoint of suppressing the back trapping phenomenon, the content of the particulate matter in the coating layer 12 is more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more, and from the viewpoint of suppressing the decrease in transparency of the coating layer 12, it is more preferably 3.0% by mass or less. In addition, the lower the content of the particulate matter, the more the increase in the haze value of the coating layer 12 can be suppressed, and also the ink loss during the formation of the coating layer can be suppressed.

[0056] The content of the particulate matter in the composition for forming the coat layer is preferably 0.1 parts by mass or more and 2.0 parts by mass or less in 100 parts by mass of the composition for forming the coat layer. When the amount of the particulate matter added is 0.1 parts by mass or more, the back trap phenomenon can be more effectively suppressed. When the amount of the particulate matter added is 2.0 parts by mass or less, the decrease in transparency of the coat layer 12 is suppressed. The content of the particulate matter is more preferably 0.2 parts by mass or more, and more preferably 1.5 parts by mass or less.

[0057] <Ink printing layer> The ink printed layer 13 is located on the coat layer 12 on the opposite side of the substrate 11 from the coat layer 12. The ink printed layer 13 is formed by applying an ink resin composition onto the coat layer 12. In this embodiment, the ink resin composition is an organic solvent-based ink, a so-called oil-based ink. However, the ink printed layer 13 may be formed by applying a so-called water-based ink onto the coat layer 12. The ink resin composition may contain, for example, a pigment, a resin, and an additive. In addition, the ink printed layer 13 is preferably a design printed layer. The design printed layer is a layer that contains a pigment and displays a visible pattern or characters, etc.

[0058] The ink-printed layer 13 may be provided on the entire surface of the coat layer 12, or may be provided on a part of the coat layer 12. The ink-printed layer 13 may be a single layer or may be multiple layers. In the configuration shown in Fig. 1, the ink-printed layer 13 includes a first ink-printed layer 13a and a second ink-printed layer 13b located on the opposite side of the coat layer 12 from the first ink-printed layer 13a. The thickness of the ink-printed layer 13 can be, for example, about 0.1 µm or more and 10 µm or less, but is not particularly limited.

[0059] The first ink-printed layer 13a is, for example, a color ink-printed layer. The first ink-printed layer 13a may be formed by applying ink of multiple colors in several separate layers. In other words, the first ink-printed layer 13a may be formed by stacking multiple printed layers of different colors.

[0060] The second ink-printed layer 13b is, for example, a white ink-printed layer. This improves the aesthetic appeal of the second ink-printed layer 13b, which is a color ink-printed layer, when the label 1 is viewed from the substrate 11 side. The second ink-printed layer 13b, which is a white ink-printed layer, may be a single layer, or may be formed of two printed layers by applying the white ink-printed layer twice.

[0061] It is preferable that the thickest portion of the ink-printed layer 13 is formed by applying ink over it seven times or less. This makes it possible to prevent blocking between the labels 1 after the ink-printed layer 13 is formed.

[0062] The ink-printed layer 13 may further contain a material that emits light when irradiated with energy rays. This allows the label 1 to be irradiated with energy rays, causing the ink-printed layer 13 to emit light together with the coating layer 12, making it easier to identify and separate the label 1 of the embodiment that has the alkali-soluble coating layer 12.

[0063] <Other layers> The label 1 according to the embodiment of the present disclosure further includes an overcoat layer 14 on the ink-printed layer 13. The overcoat layer 14 is a layer for protecting the ink-printed layer 13 from external factors. The label 1 does not necessarily have to include the overcoat layer 14. The label 1 may include another protective layer composed of a resin film or the like instead of the overcoat layer 14.

[0064] The overcoat layer 14 may be transparent or opaque, but is preferably transparent, and more preferably colorless and transparent. The overcoat layer 14 is mainly composed of, for example, an acrylic resin. In this specification, the main component refers to the component that is the largest (by weight) among the resins contained in the layer, and is, for example, 60% by weight or more, preferably 80% by weight or more, and more preferably 90% by weight or more of the total resin.

[0065] The overcoat layer 14 may optionally contain a slipping component. The overcoat layer 14 may optionally contain additives.

[0066] (Label manufacturing method) The label 1 of the embodiment can be manufactured, for example, as follows: First, prepare the substrate 11. The substrate 11 can be prepared, for example, by forming a film by a method such as an extrusion method or a calendar method, and then, if necessary, subjecting the film to a stretching treatment.

[0067] Next, the coating layer 12 is formed on one surface of the substrate 11. The coating layer 12 can be formed, for example, by applying a composition (composition for forming a coating layer) containing the resin contained in the coating layer 12 onto one surface of the substrate 11 using a known printing method, and then solidifying (preferably drying and solidifying). As the printing method, gravure printing or flexographic printing is particularly preferable.

[0068] Next, the ink-printed layer 13 is formed on the surface of the coat layer 12. The ink-printed layer 13 can be formed, for example, by applying an ink resin composition for forming the ink-printed layer 13 onto the surface of the coat layer 12 and then solidifying (preferably drying and solidifying). When the ink-printed layer 13 has multiple layers as shown in Fig. 1, the ink-printed layer 13 is formed by repeatedly applying and solidifying (preferably drying and solidifying) an ink resin composition corresponding to each of the multiple layers for each layer.

[0069] When the label 1 further includes another layer such as an overcoat layer as shown in FIG. 1, the other layer can be formed by applying a resin composition for forming the other layer onto the surface of the ink-printed layer 13 and then solidifying (preferably drying and solidifying). As described above, the label manufacturing method according to the embodiment of the present disclosure includes, in this order, a step of preparing a substrate, a step of forming a coating layer on the substrate, and a step of forming an ink-printed layer on the coating layer. Both the step of forming the coating layer and the step of forming the ink-printed layer on the coating layer are formed by the same printing method. The printing method is particularly preferably a gravure printing method.

[0070] (Energy beam irradiation and separation method) A method of irradiating the label according to the embodiment of the present disclosure and other labels with energy rays and separating the label according to the embodiment of the present disclosure from the other labels will be described.

[0071] 2 is a schematic diagram showing a state in which an energy ray is irradiated to a label according to an embodiment of the present disclosure in a predetermined dark place. First, a label group including one or more labels 1 according to an embodiment of the present disclosure and one or more other labels (not shown) is carried into the predetermined dark place 100 shown in FIG.

[0072] The group of labels carried into the dark space 100 is irradiated with energy rays U. Note that other labels are not shown in FIG. 2. The dominant wavelength of the energy rays U (the wavelength of the light having the strongest intensity (peak intensity) among the light contained in the energy rays U) is not particularly limited, but is, for example, 365 nm or more and 400 nm or less, of the energy rays U, which are specifically irradiated by the ultraviolet light irradiator 110. When the energy rays U are irradiated to the label 1, the fluorescent material contained in the coating layer 12 of the label 1 emits visible light F. In the spectrum of the energy rays U, the intensity of the wavelength component having the same maximum emission wavelength of the fluorescent material is preferably 10% or less of the peak intensity of the energy rays U. In addition, the irradiator 110 is more preferably an LED ultraviolet light irradiator. This sufficiently reduces the intensity of the visible light contained in the energy rays U irradiated by the irradiator 110, making it easy to identify the labels. It is preferable that the dominant wavelength of the energy rays U is shorter than the maximum absorption wavelength of the fluorescent material. This can reduce the influence of the irradiated energy rays.

[0073] A detector 120 is provided inside the predetermined dark place 100, the detector having a light receiving portion capable of detecting at least the light emitted by the fluorescent material contained in the coating layer 12 of the label 1. The light receiving portion of the detector 120 is preferably capable of detecting light of the maximum fluorescent wavelength of the fluorescent material contained in the label 1. The detector 120 is, for example, a camera.

[0074] The light receiving section of the detector 120 is preferably provided with a filter 130 that blocks at least a portion of the wavelength components contained in the energy rays U. This can prevent the detector 120 from detecting the wavelength components of the energy rays U in the dark space inside 100. This in turn makes it easier to detect the visible light F emitted by the fluorescent material of the labels 1. This makes it easier to identify the labels to be separated, improving the efficiency of separating the labels. In addition, it is preferable that the transmission band of the filter 130 includes the maximum fluorescent wavelength of the fluorescent material contained in the labels 1.

[0075] The filter 130 is preferably a bandpass filter. If the filter 130 is a bandpass filter, the influence of external light entering from the entrance and exit of the dark space interior 100 on the detector 120 can be reduced. In addition, the label group can be continuously introduced into the dark space interior 100 and discharged, and the sorting efficiency of the label sorting can be further improved. The central wavelength of the transmission band of the bandpass filter is preferably larger than the maximum absorption wavelength of the luminescent material contained in the luminescent layer of the label 1. In addition, the central wavelength of the transmission band of the bandpass filter is preferably close to the maximum fluorescence wavelength of the fluorescent material contained in the coat layer 12 of the label 1. If the central wavelength is close to the maximum fluorescence wavelength, the erroneous detection of ambient light by the detector is effectively suppressed, while the emission of the fluorescent material is detected. From this viewpoint, the central wavelength is, for example, 520 nm or less, preferably 490 nm or less, and more preferably 470 nm or less.

[0076] In addition, the central wavelength of the transmission band of the bandpass filter is preferably larger than the maximum fluorescence wavelength of the fluorescent material. This makes it possible to reduce the influence of the wavelength component of the energy ray in the detector 120 when ultraviolet light containing an energy ray of the same wavelength as the maximum fluorescence wavelength is irradiated on the label 1. In addition, it is also preferable that the central wavelength is equal to or greater than the maximum fluorescence wavelength or longer than the maximum fluorescence wavelength. This makes it possible to prevent the detector from erroneously detecting the energy ray (ultraviolet light) for making the fluorescent material emit light. From these viewpoints, the central wavelength is, for example, 380 nm or more, preferably 410 nm or more. The width of the transmission band of the bandpass filter is, for example, 10 to 100 nm, and preferably 30 to 90 nm. It is preferable that the lower limit of the transmission band of the bandpass filter is between the main wavelength of the irradiated energy ray U and the maximum fluorescence wavelength of the fluorescent material, between the maximum absorption wavelength and the maximum fluorescence wavelength of the fluorescent material, or between both of them.

[0077] By irradiating the label group with energy rays, the label 1 according to this embodiment can be identified by detecting the light emitted by the fluorescent material contained in the coating layer 12. On the other hand, the other labels do not contain fluorescent material and therefore cannot be detected by the detector. This makes it possible to separate the label 1 according to this embodiment from the label group.

[0078] Here, if the coating layer 12 is provided on the entire one surface of the substrate 11 in the label 1, the amount of light emitted by the fluorescent material increases whether the label 1 is irradiated with energy rays from the substrate 11 side or the opposite side to the substrate 11. This in turn makes it easier for a detector to detect the light emitted by the label 1.

[0079] There is no particular limitation on the method of separating the label 1, identified by the detection of light emission by the detector 120, from the group of labels. The label 1 may be separated from the group of labels by blowing air onto it, or the label 1 may be separated from the group of labels by being picked up by a mechanical arm.

[0080] When the label is peeled off from a beverage bottle, detergent container, or other container using the recyclable label according to this embodiment, the label is crushed and treated with a dilute alkaline aqueous solution, and the printed ink portion is very easily removed. This makes it possible to obtain a crushed product of the decolorized, colorless label. By pelletizing this crushed product, it can be used as recycled raw resin. EXAMPLES

[0081] (Creating labels) <Example 1> As the label according to Example 1, a label similar to the label having the configuration shown in FIG. 1 was produced as follows.

[0082] First, a polyethylene terephthalate film (PET film) having a thickness of 20 μm was prepared as a substrate. Next, a composition for forming a coating layer was applied onto one entire surface of the PET film using the first printing unit (first printing unit) of a gravure printing machine having multiple printing units. After that, in the process of conveying the substrate from the first printing unit to the next printing unit (second printing unit) of the gravure printing machine, the composition for forming the coating layer was dried (dried and solidified) at a temperature of 45° C. to 50° C. and a relative humidity of 50 RH% for about 1 second to form a coating layer. The conveying speed was 250 m / min.

[0083] The composition for forming the coating layer was prepared in the amounts shown in Table 1 below. The fluorescent material used was a benzoxazole-based fluorescent whitening agent with an average particle size of 11 μm, a maximum absorption wavelength of 379 nm, and a maximum fluorescence wavelength of 444 nm. The "average particle size" of the fluorescent material was measured by measuring the volume-based particle size distribution in advance and determining the particle size at which the cumulative frequency from the small particle size side reached 50%. The average particle size of the fluorescent material was specifically measured by a laser diffraction method. The average particle size of silica in the composition for forming the coating layer shown in Table 1 was measured as follows. First, the coating layer of the prepared label was photographed from the substrate side using a digital microscope. The projected area circle equivalent diameter of each of the multiple particulate substances arbitrarily extracted by analyzing the photographed image was measured. The diameters of each of the multiple particulate substances measured were arithmetically averaged on a number basis. This resulted in the average particle size of the particulate substances being measured. In addition, the composition for forming the coat layer was adjusted so that the content of the fluorescent enhancer material was 2.3 mass% and the content of silica was 1.4 mass% in the solid contents (nitrocellulose, acrylic resin, vinyl chloride-vinyl acetate copolymer, fluorescent material, and silica) of the composition for forming the coat layer.

[0084] [Table 1]

[0085] Next, the color ink resin composition was applied as an organic solvent-based color ink on the coating layer using the second printing unit, and then dried (drying and solidifying) to form a first ink printed layer. The conditions for drying and solidifying the first ink printed layer were the same as those for drying and solidifying the coating layer, except that the temperature was 60°C.

[0086] Next, using the next printing unit (third printing unit) of the gravure printing machine, a white ink resin composition containing a white ink (manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., "TFG 701 White") was applied onto the first ink printed layer, and then dried (drying and solidifying) to form a second ink printed layer. The conditions for drying and solidifying the second ink printed layer were the same as those for drying and solidifying the coat layer.

[0087] Then, using the next printing unit (fourth printing unit) of the gravure printing machine, a colorless transparent ink containing an acrylic resin as a main component (manufactured by Dainichiseika Color & Chemicals Co., Ltd., "SET Inner OP Varnish") was applied onto the second ink printing layer, and then this was dried (drying and solidifying) to form an overcoat layer. The conditions for drying and solidifying the overcoat layer were the same as those for drying and solidifying the coat layer. This completed the label of Example 1.

[0088] <Examples 2 to 5> Each of the labels according to Examples 2 to 5 was produced in the same manner as in Example 1, except that the composition for forming the coating layer was prepared in the amount shown in Table 1 above, and / or the silica in the composition for forming the coating layer was changed so that the average particle diameter of the silica in the composition for forming the coating layer was the value shown in Table 1.

[0089] <Comparative Example 1> Except for not blending silica into the composition for forming the coating layer, the label according to Comparative Example 1 was produced in the same manner as the label according to Example 1. That is, the coating layer of the label according to Comparative Example 1 does not contain any particulate matter.

[0090] <Comparative Example 2> Except for not blending a fluorescent brightening agent in the composition for forming the coating layer, the label of Comparative Example 2 was produced in the same manner as the label of Example 1. That is, the coating layer of the label of Comparative Example 2 does not contain a fluorescent brightening agent.

[0091] <Comparative Examples 3 and 4> The labels of Comparative Examples 3 and 4 were prepared in the same manner as in Example 1, except that the silica in the composition for forming the coating layer was changed so that the average particle diameter of the silica became the value shown in Table 1.

[0092] (Evaluation of luminescence) The luminescence of each label was evaluated by irradiating each label of the examples and comparative examples with ultraviolet light. The luminescence evaluation was performed by irradiating each label with ultraviolet light from the substrate side by an LED ultraviolet irradiator in a predetermined dark place in the same manner as the specific label sorting method according to the present embodiment shown in FIG. 2. The main wavelength of the ultraviolet light by the LED ultraviolet irradiator was 365 nm, and the central wavelength of the transmission band of the bandpass filter provided on the light receiving part of the camera was 460 nm (peak wavelength 470 nm, transmission band 425 nm to 495 nm). In this evaluation, the brightness value was normalized to 0 to 255, and the luminescence of the label was evaluated based on whether or not the camera could detect a light amount equal to or greater than a predetermined threshold value (250). In the above Table 1, the results of the evaluation of the luminescence of each example and each comparative example are shown according to the following criteria. ○: The camera was able to detect a light amount above the specified threshold. ×: The camera was unable to detect an amount of light equal to or greater than the predetermined threshold.

[0093] (Evaluation of cosmetic properties) The cosmetic properties of each of the labels of the Examples and Comparative Examples were evaluated by visually observing the label from the substrate side. Table 1 above shows the results of the cosmetic property evaluation of each of the Examples and Comparative Examples according to the following criteria. ◯: No fading or the like was observed in the first ink printing layer. △: Fading or the like of the first ink printing layer was observed in a very small area. ×: Many faint marks or the like were observed in the first ink printing layer.

[0094] (Evaluation of alkali release properties) The alkali release properties of the coating layer were evaluated for each label of the Examples and Comparative Examples. First, a coating layer was formed on a substrate of 5 cm x 5 cm to a size of 4 cm x 4 cm, to prepare a test piece. The coating layer had the same composition as the coating layers of each Example and Comparative Example. The test piece was immersed in a 1.5% by mass aqueous solution of sodium hydroxide kept at 80 to 90°C, stirred at 1500 rpm for 15 minutes, and the alkali release properties of the coating layer were visually observed. Table 1 above shows the results of the evaluation of the alkali release properties of each Example and Comparative Example according to the following criteria. ◯: 70% or more of the total area of ​​the coating layer viewed from the lamination direction was detached from the substrate. Δ: 30% or more and less than 70% of the total area of ​​the coating layer as viewed from the lamination direction was detached from the substrate. ×: Less than 30% of the total area of ​​the coating layer as viewed from the lamination direction is detached from the substrate, or is not detached at all.

[0095] (Evaluation of backtrap phenomenon suppression) The labels of the Examples and Comparative Examples were evaluated for the degree of suppression of the occurrence of the backtrap phenomenon. Table 1 above shows the evaluation results of the suppression of the backtrap phenomenon for each Example and Comparative Example according to the following criteria. ◯: The occurrence of the backtrap phenomenon was sufficiently suppressed. △: The occurrence of the backtrap phenomenon was partially suppressed. ×: Backtrapping occurred in many areas.

[0096] The backtrap phenomenon of the first ink printing layer will be described below. When applying the ink resin composition (color ink resin composition) for forming the first ink printing layer, a part of the coating layer on the substrate adheres to the color ink resin composition on the plate of the gravure machine and is detached from the coating layer. Due to this detachment, the color ink resin composition is not applied to the area where the part of the coating layer has been detached. This phenomenon is the backtrap phenomenon.

[0097] In the labels according to Comparative Examples 1 and 4, the back trap phenomenon occurred in many areas when the first ink printing layer was formed. As a result, the first ink printing layer was smudged, and the cosmetic properties were relatively low. This is thought to have occurred because the composition for forming the coat layer was not sufficiently solidified between the application of the composition for forming the coat layer and the application of the color ink resin composition. The poor solidification of the composition for forming the coat layer was thought to have occurred because the composition for forming the coat layer contained a fluorescent material. The coat layer of the label according to Comparative Example 1 did not contain particulate matter. Also, the coat layer of the label according to Comparative Example 4 contained particulate matter, but the average particle diameter of the particulate matter was 1 μm or less.

[0098] On the other hand, in each label according to Examples 1 to 5, the coating layer contained a fluorescent material and a particulate material, and the particulate material had an average particle size of more than 1 μm. As a result, the surface of the coating layer applied to the substrate had unevenness formed by the particulate material having an average particle size of more than 1 μm. As a result, even if the coating layer contained a fluorescent material, when applying (printing) ink onto the coating layer, the contact state between the plate for applying the ink and the coating layer changed compared to when the coating layer did not contain the particulate material, and it is considered that the backtrap phenomenon as described above did not occur. Therefore, it is considered that the occurrence of the backtrap phenomenon in the first ink printing layer was sufficiently suppressed in the labels according to Examples 1 to 5, and the ink printing layer was appropriately formed compared to the labels according to Comparative Examples 1 and 4.

[0099] In the label of Comparative Example 3, the coating layer also contained particulate matter with an average particle size of more than 1 μm, and the occurrence of the backtrap phenomenon in the first ink printed layer was sufficiently suppressed. However, in the label of Comparative Example 3, the average particle size of the particulate matter in the coating layer was more than 100 μm, so fading was observed in the first ink printed layer formed on the coating layer, and the cosmetic quality of the label was poor.

[0100] On the other hand, the particulate matter contained in the coating layer had an average particle size of 100 μm or less in each of the labels according to Examples 1 to 5. As a result, no smearing or the like was observed in the first ink printed layer formed on the coating layer, and the deterioration of the aesthetic appeal of the label due to the particulate matter contained in the coating layer was suppressed.

[0101] In the above-described embodiments and examples, configurations that can be combined with each other may be appropriately combined.

[0102] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. [Explanation of symbols]

[0103] 1 label, 11 substrate, 12 coating layer, 13 ink printing layer, 13a first ink printing layer, 13b second ink printing layer, 14 overcoat layer, 100 inside dark place, 110 irradiator, 120 detector, 130 bandpass filter.

Claims

1. A substrate; a coating layer provided on the substrate, the coating layer including a resin having an acid value of 40 mgKOH / g or more and 150 mgKOH / g or less and a fluorescent material; an ink printing layer located on the coating layer on the opposite side of the substrate from the coating layer; A recyclable label, wherein the coating layer further contains particulate matter, and the particulate matter has an average particle size of more than 1 μm and not more than 100 μm.

2. 2. The recyclable label of claim 1, wherein the particulate material is silica.

3. 2. The recyclable label of claim 1, wherein the resin is an acrylic acid copolymer resin.

4. The recyclable label of claim 1 , wherein the fluorescent material is a benzoxazole-based compound.

5. the content of the fluorescent material in the coating layer is 0.3% by mass or more and 8.0% by mass or less, The recyclable label according to claim 1 , wherein the content of the particulate matter in the coating layer is from 0.1% by mass to 5% by mass.

Citation Information

Patent Citations

  • Biaxially oriented polyester film

    JP2019127536A

  • Label, method for removing ink layer from label, and method for manufacturing label

    WO2021246230A1